단전호흡이 혈액투석환자의 우울, 불안 및 피로에 미치는 효과 - 정미현(Mi-Hyun Jeong) (한국콘텐츠학회 논문지, 12(4), 2012)
This study was performed to examine the effects of Dan Jeon Breathing on depression, anxiety and fatigue of hemodialysis patients. This study used the nonequivalent control group pretest-posttest design. Before applying the Dan Jeon Breathing program, the patients were divided into the experimental group and the control group, respectively, and were requested to report their self-ratings to measure their depression, anxiety and fatigue. The Dan Jeon Breathing program was given to both groups for 60 minutes a day and 2 times a week for 12 weeks. The data collected from the program were analysed by means of ${χ}^2$ test, Fisher's exact probability test, Shapiro-Wilk, t-test and Mann-Whitney U test. The analyses revealed that the depression (t=-2.459, ${ρ}$=.019) and anxiety (t=-2.541, ${ρ}$=.016) levels of the experimental group decreased after Dan Jeon Breathing compared to those of the control group. The difference in fatigue level was statistically insignificant (Z=-1.871, ${ρ}$=.061), though. From the above results, it was verified that Dan Jeon Breathing could be used as nursing intervention for hemodialysis patients to mitigate their depression and anxiety. 본 연구는 J도에 소재한 2개 의료기관에서 주 1회 이상 혈액투석을 받고 있는 환자로서 1회 60분씩, 주 2회, 12주간 단전호흡 프로그램을 적용한 실험군 18명과 대조군 19명을 대상으로 비동등성 대조군 전-후 설계의 유사실험연구(Quasi-experimental design)이다. 단전호흡 프로그램이 혈액투석환자의 우울과 불안 및 피로에 미치는 효과를 규명하고자 우울(Zung, 1965)과 불안(Spielberger, 1975) 그리고 피로(Lee, Hick and Nino-Murcia, 1991)도구를 사용하여 종속변수를 측정하였으며, 간호중재로서의 가능성을 검증하였다. 연구결과, 단전호흡 프로그램을 실험처치한 실험군에서는 대조군보다 우울과 불안 정도의 감소는 통계적으로 유의하였으나 피로 정도 감소에는 유의하지 않았다. 따라서 단전호흡 프로그램은 만성질환자인 혈액투석환자의 우울과 불안을 감소시킬 수 있는 간호중재로 활용할 수 있을 것으로 사료된다.